After Brexit: Britain#xB4;s Future (Global Journal of Management and Business Research, 2021)
After 43 years as a member first of the European Community and then the European Union (EU), the United Kingdom decided, in what is assumed to be the most democratic way possible, to leave this relationship. The British public have voted against their own interests. People across Europe, and indeed throughout the world, are afraid. Above all they are afraid of globalisation, which they believe has brought the threat of the other into their daily lives and has undermined their livelihoods, while benefiting only an elite few.
Keywords: brexit; europe; great britain